Experienced Harm from Other People's Drinking: A Comparison of Northern European Countries - Inger Synnøve Moan; Elisabet E. Storvoll; Erica Sundin; Ingunn Olea Lund; Kim Bloomfield; Ann Hope; Mats Ramstedt; Petri Huhtanen; Sveinbjörn Kristjánsson (SAGE Publishing, 2015)
Objective This study addresses how experienced harm from other people's drinking varies between six Northern European countries by comparing 1) the prevalence of experienced harm and 2) the correlates of harm. Method The data comprise 18ȓ69-year olds who participated in general population surveys in Denmark, Finland, Iceland, Norway, Sweden, and Scotland during the period 2008-2013. Comparative data were available on five types of harm: physical abuse, damage of clothes/belongings, verbal abuse, being afraid, and being kept awake at night. Results This study shows that harms from other's drinking are commonly experienced in all six countries. Being kept awake at night is the most common harm, while being physically harmed is the least common. The proportions that reported at least one of the five problems were highest in Finland and Iceland and lowest in Norway, but also relatively low in Sweden. Across countries, the level of harm was highest among young, single, urban residents, and for some countries among women and those who frequently drank to intoxication themselves. Conclusions The study revealed large differences in the prevalence of harm in countries with fairly similar drinking cultures. However, the correlates of such experiences were similar across countries. Possible explanations of the findings are discussed, including differences in study design.